(untitled) (Journal of Nobel Medical College, 2024)
Background: Examination of blood smears and various hematologic parameters is the first step in assessment of hematologic function and diagnosis of possible underlying diseases. The aim of this study was to identify artefacts in stored red blood cells and classify the occurrence of such alterations according to the age of the stored sample. This studyalso aimed to note the changes in platelet count dispatched by automated hematology coulter in such stored blood samples. Material and Methods: A prospective cross sectional study was conducted from the EDTA anticoagulated blood samples of 100 patients received in the department of Pathology after receiving ethical approval from the institutional review committee. All the samples were analyzed in 4 occasions i.e. within 2 hours, at 24 hours, at 48 hours and at 96 hours. Analysis was carried out by Sysmex 5 part analyzer for platelet counts and the Leishman stained blood films were examined to note changes in the erythroctyte morphology. Results: There was alterationsin platelet counts in 22% cases between 2-hour samples and other samples. The red blood cell morphology was not different among 2 hours samples and 24 hours sample. However, the red blood cell morphology was altered in 48 hours samples and 96 hours samples. Conclusion: Storage of EDTA anticoagulated blood even upon refrigeration can cause changes in platelet counts as well as morphology of red blood cells. Changes in red blood cells are not significant till 24 hours while the platelet counts may alter within 24 hours.